A Multistage Stochastic Programming Model with Multiple Objectives for the Optimal Issuance of Corporate Bonds - Yang, Ruicheng; Hu, Zinan (Discrete dynamics in nature and society, 2022)
Large corporations usually cover their capital and operating expenses by issuing bonds with fixed rates and different maturities. This paper proposes a multistage stochastic programming (MSP) model with multiple objectives to optimize bond issuance by satisfying the three common objectives of corporate managers, as follows: (i) Minimizing expected discounted cost under cash liquidity and financial leverage risk constraints. (ii) Minimizing financial leverage risk under expected discounted cost and cash liquidity risk constraints. (iii) Minimizing cash liquidity risk under expected discounted cost and financial leverage risk constraints. We measure liquidity risk as conditional payment-at-risk (CPaR), according to the corporation’s financial characteristics. Financial leverage risk is captured by conditional financial leverage-at-risk CFLaR, which we design based on conditional value-at-risk (CVaR). Through empirical analysis of a company in China, we explore the efficient frontier curves for the three above objectives and provide the corresponding issuance compositions of an optimal bond portfolio. Our MSP model offers guidance for corporations on achieving a trade-off between cost and risk when issuing corporate bonds.